Organisational management of hospital blood transfusion services in Nairobi County, Kenya: Evidence of implementation - Anne N. Mbuthia; Eunice M. Mwangi; Musa O. Ong'ombe (AOSIS, 2019)
Background: The World Health Organization in 2002 recommended implementation of a quality system for national blood programmes to ensure adequate and safe blood products to patients. Key elements of the quality system include organisational management, standards, documentation, training and assessment. Objectives: The aim of this study was to describe the extent to which organisational management, which is the first element of a quality system, has been implemented in hospitals in Nairobi County, Kenya. Methods: A descriptive, cross-sectional study design was used. Sixty health workers were selected as respondents from 15 hospitals that provide blood transfusion services in Nairobi County. The data collection period was from June to August 2015 and the data were analysed in 2016. Results: Faith-based hospitals had the lowest level of organisational management implementation (33.3%), private hospitals had 42.5%, whereas government hospitals had the highest implementation (60%). The extent of implementation was based on performance of the senior management team, overall rated by the respondents at 40.1%, establishment of hospital transfusion committees in nine (60%) of the hospitals and appointment of key staff - quality officers in three (20%) hospitals and blood transfusion specialists in six (40%) hospitals. These key staff were instrumental in steering the quality system and ensuring sound blood transfusion practices. Conclusion: The implementation of quality management systems in hospital blood transfusion services can be improved through commitment from senior management teams, who should provide the necessary resources for employment of key staff and establish and empower hospital transfusion committees to guide the blood transfusion services.